Molecular characterization of Cryptosporidium spp. in dairy calves from the state of So Paulo, Brazil - Meireles, Marcelo Vasconcelos [UNESP]; de Oliveira, Fernando P. [UNESP]; Teixeira, Weslen Fabricio P. [UNESP]; Coelho, William M. D. [UNESP]; Mendes, Luiz Claudio Nogueira [UNESP] (Springer, 2011)
Cryptosporidiosis is a common protozoan disease observed in a wide range of vertebrate hosts, including ruminants. Cattle can be a potential reservoir of Cryptosporidium spp., leading to environmental contamination with oocysts of zoonotic species. The molecular characterization of Cryptosporidium spp. isolated from cattle from the state of So Paulo, Brazil, was accomplished using nested polymerase chain reaction for amplification of fragments of the 18S rRNA gene and the glycoprotein GP60 gene, following sequencing of amplified fragments. Positivity for Cryptosporidium was found in 10.7% (21/196) of the samples. Four species of Cryptosporidium were identified: C. andersoni, C. bovis, C. parvum subtype IIaA15G2R1, and C. ryanae. To the best of our knowledge, this is the first report of infection by C. ryanae and C. parvum IIaA15G2R1 in cattle from Brazil.